Augmented Reality Building Blocks: Meningkatkan Kreativitas Anak Usia Dini melalui Permainan Konstruktif Digital-Fisik - Malim Soleh Rambe; Asmaryadi Asmaryadi; Sukatno Sukatno; Nurhasanah Pardede; Vitria Larseman Dela; Erlina Harahap; Khairul Amri; Harun Arrasyd (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study develops and tests the effectiveness of augmented reality building blocks (AR-Block) in increasing the creativity of 5-6 year old children at Darul Hasan IT Kindergarten, Padangsidimpuan City. Using a mixed-methods approach and a pretest-posttest control group design, the sample was purposively selected (N=40) and divided into an experimental (AR-Block) and a control (conventional block) group. The instruments included: (1) the Digital Creativity Assessment Tool (DCAT) to measure fluency, flexibility, and originality of ideas, (2) eye-tracking for engagement analysis, and (3) IoT sensors on the blocks to record interaction patterns. Results showed a significant increase in the experimental group (t=6.32, p<0.001, d=1.5), with the largest effect on originality (a 42% increase). Qualitative analysis revealed three mechanisms of technological influence: (1) AR visual scaffolding stimulates idea exploration, (2) real-time system feedback enhances intrinsic motivation, and (3) digital collaboration develops social-creative skills. Practical implications include: (1) a hybrid physical-digital model for early childhood education (ECE), (2) teacher training in AR integration, and (3) a digital creativity framework based on play-based learning. This research enriches the literature on children's educational technology with empirical evidence that multimodal interaction design can optimize creativity development.